Mechanical circulatory support in pediatrics. (3rd May 2016) - Steffen, Robert J.; Miletic, Kyle G.; Schraufnagel, Dean P.; Vargo, Patrick R.; Fukamachi, Kiyotaka; Stewart, Robert D.; Moazami, Nader
ABSTRACT: End-stage heart failure affects thousands of children yearly and mechanical circulatory support is used at many points in their care. Extracorporeal membrane oxygenation supports both the failing heart and lungs, which has led to its use as an adjunct to cardiopulmonary resuscitation as well as in post-operative cardiogenic shock. Continuous-flow ventricular assist devices (VAD) have replaced pulsatile-flow devices in adults and early studies have shown promising results in children. The Berlin paracorporeal pulsatile VAD recently gained U.S. Food and Drug Administration approval and remains the only VAD approved in pediatrics. Failing univentricular hearts and other congenitally corrected lesions are new areas for mechanical support. Finding novel uses, improving durability, and minimizing complications are areas of growth in pediatric mechanical circulatory support.